Nilai-Nilai Pendidikan Sabar, Ridha, dan Tawakal Dalam Q.S. Al-Baqarah Ayat 286 Perspektif Tafsir Ibnu Katsir - Muhammad Fathur Rozzaq Nurtri; Akhmad Alim; Dedi Supriadi (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
Islamic education plays a strategic role in shaping students' character, spirituality, and psychological resilience. However, the rapid development of globalization, technological advancement, and digital culture has created various moral challenges among young generations. One of the most prominent issues is the emergence of a hedonistic lifestyle characterized by materialism, consumerism, and excessive pursuit of worldly pleasure. This phenomenon highlights the importance of strengthening Islamic educational values derived from the Qur'an as guidance for character building.This study aims to analyze the educational values of patience (sabr), contentment (ridha), and reliance on Allah (tawakal) contained in Surah Al-Baqarah verse 286 based on Ibn Kathir’s interpretation and to examine their relevance to contemporary Islamic education. The research employs a qualitative approach using a library research method. Primary data were obtained from Tafsir Al-Qur’an Al-‘Azhim by Ibn Kathir, while secondary data were collected from books, journal articles, and other relevant sources.The findings reveal that Surah Al-Baqarah verse 286 emphasizes that Allah does not burden any soul beyond its capacity. The verse contains three major educational values: patience, contentment, and reliance on Allah. Patience contributes to mental resilience and self-control, contentment develops gratitude and emotional stability, while reliance on Allah fosters optimism, self-confidence, and a balance between effort and trust in divine will. These values are highly relevant to contemporary Islamic education as they provide solutions to moral degradation, character crises, and the influence of hedonistic lifestyles among students